AMBRA1 Regulation: An Overview - Hassan Ali Alhelal1, Azhar Abdullah Alshehab 2 , Hashem Abbas Almuslam 2, Mohammed Mansour Altaher 3 , Aqeela Hassan Alhababi4, Alya Yousef Ali Alyousef2, Mousa Sulaiman Alyousef 5, Rahma Ali Mohammed Alherz2, Shaima Abdullah Alhabib2, Yosef Ali Anasser2; Abdujaleel Ahmad Allowaim2, Fahad Ali Alobaid2, Zainab Nasser Jasim Almubarak2, Zahrah Mohammad Alibrahim2, Zainab Mohammad Alibrahim2 (International Journal of Scientific Research and Innovative Studies, 2024)
AMBRA1 (DCAF3) (Activating Molecule in Beclin-1-Regulated Autophagy) is a key regulator in the autophagy pathway, playing a critical role in cellular homeostasis and survival. This review provides a comprehensive overview of AMBRA1 regulation, focusing on its involvement in autophagy, its interaction with other proteins, and its implications in health and disease. Keywords: AMBRA1, health, regulation. Received Date: April 18, 2024 Accepted Date: May 16, 2024 Published Date: June 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/168 DOI: https://doi.org/10.5281/zenodo.12803083